Effect of harmane on the convulsive threshold in epilepsy models in mice - ARICIOĞLU, FEYZA (NEW YORK ACAD SCIENCES, 2003)
The study investigated the activity of harmane on maximal electroshock seizures (MES) and seizures induced by pentilentetrazole (PTZ) in mice. Initial studies established convulsive current 50 (CC50) values or MES and effective dose 50 (ED50) for PTZ to produce seizures. Harmane (2.5, 5.0, or 10 mg/kg intraperitoneally) increased the threshold of seizures in MES dose-dependently. The convulsions produced by PTZ were decreased by the low dose of harmane (2.5 mg/kg), but the high dose of harmane (10 mg/kg) resulted in worse grade V convulsions followed by more lethality compared with PTZ alone. Therefore, harmane seems to be protective against grand mal seizures in the MES model but not against a petit mal seizure model (PTZ) in mice.
Keywords: harmane; maximal electroshock; pentylenetetrazol; imidazoline; benzodiazepine; monoamine oxidase; ELECTRICAL STIMULATION; SEIZURE ACTIVITY; BETA-CARBOLINES; RATS; NOREPINEPHRINE; BINDING; 5-HT